Improving the quality of in-work education for students from the comprehensive general medicine residency - López Borges, Yasmina; Betancourt Fuentes, Lizandra; Creagh Almiñan, Yoasmy; Nápoles Reyna, Leyanis; Granada Rodríguez, Wilser; Vega Fiol, Midiala (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Background: the preparation of Higher Education teachers is a fundamental premise to carry out a teaching-learning process with the required quality. Objective: Design a system of actions to improve the quality of education at work from the Comprehensive General Medicine residency.Method: a quantitative-qualitative educational study was carried out in the period February-July 2023. From a universe of 107 residents, a 40 % sample was taken by simple random sampling, being represented by 42 professionals; to whom an initial survey designed by the author and previously validated by a committee of experts was applied. Theoretical, empirical and statistical methods were used.Results: inadequate and inadequate knowledge predominated in relation to knowledge, procedures and attitude in relation to the teaching-educational process. The lack of teaching, scientific and research skills; the insufficient number of pedagogical research in the institution and the high enrollment of students in teaching settings were pointed out as the main causes. A system of actions was designed based on postgraduate courses, increasing professional development activities in the methodological teaching plan, increasing control visits to offices and the support of training specialists and holding workshops for each document. Regulations issued by the national direction.Conclusions: the designed system of actions should contribute to the improvement of the teaching-learning process in undergraduate education, promote the scientific- professional and pedagogical development of professionals.